Sosialisasi Pemanfaatan Internet banking Untuk Meningkatkan Kinerja Penjualan Usaha Mikro Di Desa Ngijo Kecamatan Tasikmadu Kabupaten Karanganyar - sriyanto sriyanto; sutianingsih sutianingsih; Rima Parawatibala (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
Ngijo Village, Tasikmadu District, Karanganyar Regency has various potentials, one of which is the snack industry. Observation results, Partners have a good opportunity as evidenced by an increase in sales turnover every month. Partners have taken advantage of marketplaces such as Shopee, Tokopedia, OLX. Partner's understanding of banking digitalization is important to have, the problem is that Partners have not used internet banking. Community Service Activities carried out on Saturday 23 July 2022 in the form of a Workshop aimed at introducing internet banking as a strategy to improve sales performance. In practice, all partners are very enthusiastic about participating in the Workshop. By looking at the performance of Partners participating in simulations and doing exercises, it shows an increase in understanding where student partners have gained a good understanding of the use of internet banking to improve sales performance.